A Comparison of Product Weight Method and Simple Addition Weight Method in Employee Selection System - Alwani, Adie G.; Avianto, Donny (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2023)
Tegar Mandiri Steam Ironing Service is a business operating in the steam ironing service industry, located in the Boyolali area, specifically in Dlingo Village, Mojosongo Subdistrict, Boyolali Regency, Central Java.